1979
DOI: 10.1073/pnas.76.1.504
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies from patients with myasthenia gravis recognize determinants unique to extrajunctional acetylcholine receptors.

Abstract: We have examined the interaction between sera from patients with myasthenia gravis and acetylcholine receptor (AcChoR) purified from normal and denervated rat skeletal muscles [junctional receptor (UR) and extrajunctional receptor (EJR), respectively]. Eight of ten myasthenic sera had titers against EJR that were significantly higher (1.1-2.4 times) than their titers against JR. The antireceptor titers of these sera ranged from 2 to 102 nM. Although activities of three other sera were too low (<1 nM) to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 33 publications
(30 reference statements)
2
49
0
Order By: Relevance
“…Although the main ACh-binding sites are on the ␣ subunits, they lie at the ␣/␦ and ␣/␥ interfaces: the distinctive ␣/␥ site of the fetal isoform seems to be the target for the inhibitory antibodies (Riemersma et al, 1997). Similar antibodies were found in one MG serum using rat fetal AChR in an early study (Weinberg and Hall, 1979), although they bound to both adult and fetal isoforms when human AChR was used (Burges et al, 1990). These inhibitory antibodies compete with 125 I-␣-BuTx for binding to one of its two sites, making their detection with 125 I-␣-BuTx-AChR more difficult, although we tried to overcome this difficulty by overlaying the filters with unlabeled AChR and adding 125 I-␣-BuTx subsequently.…”
Section: Fetal-specific Abs In Arthrogryposissupporting
confidence: 48%
“…Although the main ACh-binding sites are on the ␣ subunits, they lie at the ␣/␦ and ␣/␥ interfaces: the distinctive ␣/␥ site of the fetal isoform seems to be the target for the inhibitory antibodies (Riemersma et al, 1997). Similar antibodies were found in one MG serum using rat fetal AChR in an early study (Weinberg and Hall, 1979), although they bound to both adult and fetal isoforms when human AChR was used (Burges et al, 1990). These inhibitory antibodies compete with 125 I-␣-BuTx for binding to one of its two sites, making their detection with 125 I-␣-BuTx-AChR more difficult, although we tried to overcome this difficulty by overlaying the filters with unlabeled AChR and adding 125 I-␣-BuTx subsequently.…”
Section: Fetal-specific Abs In Arthrogryposissupporting
confidence: 48%
“…It should be noted that the AChR present on cultured muscle cells is of the extrajunctional type. The electrophysiological, metabolic, and biochemical, properties of extrajunctional AChR are known to differ from those of junctional AChR (26,27) and recent studies suggest that there is an immunological difference between the two receptor types (28 reported that mice immunized with T. californica AChR did develop EMG and that the response was strain dependent in that AKR mice seemed to be very susceptible to EMG, and other strains, particularly those possessing the H-2 q and H-2 s haplotypes, seemed to be resistant to EMG. Our studies are compatible with the results of Fulpius et al (29) in that BALB/c mice appear to be a low EMG-susceptibility strain and exhibit a high serum concentration of anti-AChR antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of AChRs results from several different processes. Relatively few antibodies directly block the function of the ACh-induced ion channel, but these antibodies can be important in some patients [28,29] and some MG sera appear to have a transient inhibitory effect on AChR function in vitro. [30] A more important mechanism is a reduction in AChRs due to the crosslinking of AChRs by divalent antibodies.…”
Section: Mechanisms Of Diseasementioning
confidence: 99%